PERANCANGAN MEDIA PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI MENGGUNAKAN NEARPOD PADA KELAS IX DI SMPN 2 BUKIT TINGGI - Rasiman Padang; Efriyanti, Liza; Zakir, Supratman; Okra, Riri (Jurnal Informatika Medis, 2024)
Unavailability of supporting teaching materials for students based on learning media applications limited to the knowledge contained in textbooks. Limited sharing of learning material files and assignments when the teacher is unable to attend results in students not being able to study independently. There is no update in the learning media, information communication technology in the learning process, it is not updated. This research aims to develop and produce communication information technology learning media using nearpod in class IX at SMP Negeri 2 Bukittinggi that is valid, practical and effective. This research method is Research and Development with four 4D stages. The results show that the learning media for information and communication technology uses nearpod in class IX at SMP Negeri 2 Bukittinggi; validity test from 4 experts in the field showed a value of 0.86 in the valid category; practicality test from 2 experts showed a value of 0.85 in the very practical category; The effectiveness test of 19 students in information communication technology learning showed a value of 0.91 in the high effectiveness category so that information communication technology learning media products were considered appropriate and could be used in information communication technology learning.